Moving modernisms motion, technology, and modernity - Bradshaw, David 1955-2016; Marcus, Laura 1956-2021; Roach, Rebecca 1983- (Oxford University Press, 2016)
This book opens up the many dimensions and arenas of modernist movement and movements: spatial, geographical and political: affective and physiological; temporal and epochal; technological, locomotive and metropolitan; aesthetic and representational. Individual essays explore modernism's complex geographies, focusing on Anglo-European modernisms while also engaging with the debates engendered by recent models of world literatures and global modernisms. From questions of space and place, the volume moves to a focus on movement and motion, with topics ranging from modernity and bodily energies to issues of scale and quantity. The final chapters in the volume examine modernist film and the moving image, and travel and transport in the modern metropolis. 'Movement is reality itself', the philosopher Henri Bergson wrote: the original and illuminating essays in this book point in new ways to the realities, and the fantasies, of movement in modernist culture